Tijauan Hukum Yang Menyediakan Bisnis Menggunakan Stiker SNI Pada Helm Tanpa Mengenai Badan Standarisasi - Rildo Rafael Bonauli; Sandy Thrisna Manueln Situmeang (Wajah Hukum, 2020)
Indonesian national standard ( sni ) constituting a standard applied by the standardisasi national and prevail in those regions of the unitary state of the republic of indonesia .Formulated by the technical standard komite-komite consisting of multiple stakeholders whether it is the government , academics , industry and the competent dibidangnya masing-masing severe .In general there are 3 grouping certification activities based on sni can do is: sitem management certification , the certification on enterprise management system for example berdasarnya ( sni iso 9001 , 14001 , 22000 , haccp , etc ); product certification , the certification on a product produced the company based on certain products for example sni sni: 2007 1811 to a helmet , sni 3554: 2015 bottled water for drinking , sni 2054: 2014 to steel tulangan concrete , and other produk-produk; personnerl certification , the auditor sertifkasi against personnel competence for example , ppc , oil and gas workers , electric power